2021
DOI: 10.1088/2515-7655/abbd34
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of an iridium oxygen evolution catalyst by titanium oxides

Abstract: The anodic oxygen evolution reaction (OER) has significant importance in many electrochemical technologies. In proton exchange membrane water electrolyzers it plays a pivotal role for electrochemical energy conversion, yet sluggish kinetics and the corrosive environment during operation still compel significant advances in electrode materials to enable a widespread application. Up-to-date Iridium is known as the best catalyst material for the OER in acidic media due to its relatively high activity and long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 53 publications
4
56
0
Order By: Relevance
“…The stability we measure for s-400 °C IrO 2 (crystalline Ir 18 O 2 sputter-deposited at 400 °C) is lower than some previously reported values (∼7 × 10 4 in our case compared to 10 5 –10 6 ). 38 The difference might be due to the stability number being lower at the low current densities probed by chip EC-MS or due to imperfect electrolyte exchange in the cell when the electrolyte was sampled, which could cause some of the metal dissolution from the ramp-up period to remain in the cell and cross-contaminate the steady-state electrolyte samples. Ruthenium-based samples lie well below the y = x line, meaning that they lose ruthenium atoms to dissolution much faster than they incorporate lattice oxygen into the O 2 evolved.…”
Section: Resultsmentioning
confidence: 99%
“…The stability we measure for s-400 °C IrO 2 (crystalline Ir 18 O 2 sputter-deposited at 400 °C) is lower than some previously reported values (∼7 × 10 4 in our case compared to 10 5 –10 6 ). 38 The difference might be due to the stability number being lower at the low current densities probed by chip EC-MS or due to imperfect electrolyte exchange in the cell when the electrolyte was sampled, which could cause some of the metal dissolution from the ramp-up period to remain in the cell and cross-contaminate the steady-state electrolyte samples. Ruthenium-based samples lie well below the y = x line, meaning that they lose ruthenium atoms to dissolution much faster than they incorporate lattice oxygen into the O 2 evolved.…”
Section: Resultsmentioning
confidence: 99%
“…[15] TiO 2 is specifically chosen as a support given its chemically stability against dissolution under anodic working conditions in PEMWEs. [20] Outstanding performances of PEMWEs using IrO 2 -TiO 2 commercial catalysts and a Nafion 212 membrane (51 µm thick) were reported by Gasteiger et al, [15,16] showing current density of 6 A cm −2 at a cell voltage of 1.92 V. However, no gas cross-over evaluation was performed in that study. Nevertheless, by thoroughly analyzing cell performance using IrO 2 -TiO 2 commercial catalyst at various loadings (0.2-5.4 mgIr cm −2 ), Gasteiger et al [15] demonstrated that the performance of the studied cells could not meet the requirement for de-carbonization of the entire transport sector until 2100.…”
Section: Introductionmentioning
confidence: 81%
“…This system has been further improved by various metal-support combinations with mechanistic studies, [339] morphology controls, [340] surface treatments, [341,342] and selection of various oxides. [343][344][345] In addition to the stabilization effect on active metal nanoparticles, there have been many reports on the promotive effects of metal oxide supports in the increased reaction kinetics, such as in methanol oxidation reaction (MOR). [346] Various multimetallic catalysts showed enhanced performance in combination with different oxide supports, which has been explained by two main reasons.…”
Section: Nanoparticle-support Interaction By the Electronic Effectmentioning
confidence: 99%
“…This system has been further improved by various metal‐support combinations with mechanistic studies, [ 339 ] morphology controls, [ 340 ] surface treatments, [ 341 , 342 ] and selection of various oxides. [ 343 , 344 , 345 ]…”
Section: Considerations For Electrocatalytic Applications Of Nmmnsmentioning
confidence: 99%